Diffuse cutaneous leishmaniasis in HIV positive woman - Niloofar Mehrolhasani (Our Dermatology Online, 2014)
A 29 years old woman was come to our dermatology clinic with a 1 month history of lesions on her face and extremity. She was diagnosed with HIV from 6 months ago and since then she was on treatment for HIV. Clinical examination was notable for painless indurated erythematous plauqe on her face and erythematous papule on her extremities (Fig. 1, 2). The Patient was from Bam (Iran), in which cutaneous leishmaniasis is endemic. She has history of cutaneous leishmaniasis 4 years ago. In that time she was treated successfully with injections of sodium stibogluconate.